2004
DOI: 10.1128/jcm.42.2.778-783.2004
|View full text |Cite
|
Sign up to set email alerts
|

PCR Assays for Identification of Coccidioides posadasii Based on the Nucleotide Sequence of the Antigen 2/Proline-Rich Antigen

Abstract: A conventional nested PCR and a real-time LightCycler PCR assay for detection of Coccidioides posadasii DNA were designed and tested in 120 clinical strains. These had been isolated from 114 patients within 10 years in Monterrey, Nuevo Leon, Mexico, known to be endemic for coccidioidomycosis. The gene encoding the specific antigen 2/proline-rich antigen (Ag2/PRA) was used as a target. All strains were correctly identified, whereas DNA from related members of the family Onygenaceae remained negative. Melting cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(52 citation statements)
references
References 23 publications
0
51
0
1
Order By: Relevance
“…A significant challenge for our laboratory, found when reviewing the available literature on Coccidioides PCR methods (6,9,14), was the personnel time required to perform the separate extraction step and how to fit this testing into our daily workflow. An additional issue was that the extraction and PCR testing from other researchers were performed on instruments not available in our laboratory.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A significant challenge for our laboratory, found when reviewing the available literature on Coccidioides PCR methods (6,9,14), was the personnel time required to perform the separate extraction step and how to fit this testing into our daily workflow. An additional issue was that the extraction and PCR testing from other researchers were performed on instruments not available in our laboratory.…”
Section: Discussionmentioning
confidence: 99%
“…Methods include traditional serology testing for immunodiffusion tube precipitin (TP) or complement fixation (CF) antibody, enzyme immunoassays, culture, and histopathology (6). Serology testing for Coccidioides is helpful but has limitations for diagnosing current, active infections, since antibodies may be slow to increase to detectable levels, especially in immunocompromised patients (7,8).…”
Section: Alley Fever Caused By the Dimorphic Fungi Coccidioides Immmentioning
confidence: 99%
“…; thus, analysis of other regions should be considered (37,84). In addition, false-positive results with specific H. capsulatum primers and difficulties in identifying Coccidioides in formalin-fixed tissues have been reported (15,17). A Mayo Clinic study of 147 FFPE samples showed that histology found more coccidioidomycosis cases than PCR (19).…”
Section: Pcr-based Methodsmentioning
confidence: 99%
“…In addition to Coccidioides immitis, Coccidioides posadasii has been described recently as the likely etiologic agent of coccidioidomycosis originating outside California (30).…”
Section: Fungal Infections Infections Caused By Coccidioides Immitismentioning
confidence: 99%